Measuring reservation prices for bundles of fixed telecommunications services - Maciej Sobolewski; Tomasz Kopczewski (International Telecommunications Society (ITS), 2015)
Bundling becomes a dominant sales strategy in telecommunications. Dual and triple-play packages are increasingly popular among subscribers. From operators' perspective, a core issue in bundling design is the knowledge about how consumers value packages. In this paper we focus on elicitation of subscribers willingness to pay for bundles of fixed telecommunication services composed of telephony, Internet and paid TV. We conduct a stated preference discrete choice experiment on a sample of subscribers in Poland, to model subscription choices over packages of fixed services. We obtain estimates of mean willingness to pay as well as entire distributions of reservation prices for single services and possible combinations of bundles. We find that mean WTP for fixed telephony as a stand-alone service or an add-on to bundle is zero. This result suggest that fixed telephony has already become an obsolete service. Out of the three fixed services, Internet generates the biggest value for customers, driving up valuations of bundles. WTP for Internet is much higher than actually paid prices, leaving space for increase of profits. In contrast fixed telephony and pay TV seem to be overpaid which may create a pressure on operators' revenue.
Keywords: C25; D12; L96; 330; Bundling; stated choice experiment; willingness to pay; fixed telephony; fixed broadband; pay TV; dual play; triple play; fixed-to-mobile substitution